2022
DOI: 10.37284/eaje.5.1.561
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Acid Red 88 from an Aqueous Solution Using Kaolinite Clay by Adsorption Process

Abstract: Dyes are hazardous contaminants normally found in industrial wastewaters necessitating costly and complex technologies for their removal. In this study, clay was used as an adsorbent in the removal of anionic acid red 88 (AR 88) dye from industrial wastewaters by adsorption. The dye removal efficiency and adsorption capacity of clay was studied by batch experimentation with respect to parameters of dye initial concentration, clay dosage, contact time, and pH. The dye removal efficiency of AR 88 improved with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…Hence 60 min of the biochar is considered the best and most efficient contact time. Similar studies were conducted by Dadebo and Obura in which they experimented on the effect of contact time on the removal of Acid Red 88 dye using Kaolinite Clay and found that the removal efficiency increased with respect to contact time up to the point of equilibrium after which there was no increase in removal efficiency with any increase in contact time (Dadebo and Obura, 2022).…”
Section: Impact Of Time On Removal Efficiencysupporting
confidence: 71%
See 1 more Smart Citation
“…Hence 60 min of the biochar is considered the best and most efficient contact time. Similar studies were conducted by Dadebo and Obura in which they experimented on the effect of contact time on the removal of Acid Red 88 dye using Kaolinite Clay and found that the removal efficiency increased with respect to contact time up to the point of equilibrium after which there was no increase in removal efficiency with any increase in contact time (Dadebo and Obura, 2022).…”
Section: Impact Of Time On Removal Efficiencysupporting
confidence: 71%
“…Hence 75 ppm of the AR dye is considered the best and most efficient concentration to be set before the starting of the experiment. Similar studies were conducted by Dadebo and Obura in which they experimented on the effect of initial dye concentration on the removal of Acid Red 88 dye using Kaolinite Clay and found that the removal efficiency decreased with respect to initial dye concentration due to the elevated collision between the adsorbent and adsorbate (Dadebo and Obura, 2022).…”
Section: Impact Of Dye's Initial Concentration On the Removal Efficiencysupporting
confidence: 68%